Impact of Bifidobacterium lactis supplementation on fecal microbiota in infants delivered vaginally compared to Caesarean section - Tetty Yuniaty; Fiva Kadi; Hadyana Sukandar; Mifta Novikasari; Pensri Kosuwon; Enea Rezzonico; Paiboon Piyabanditkul; Leilani Lestarina; Marco Turini (Paediatrica Indonesiana, 2013)
Background It has been reported that infants born by Caesareansection have altered gut microbiota, with lower n umbers ofbifidobacteria and Bacteroides, compared to that of infants whowere delivered vaginally. Probiotic supplementation has beenreported to have beneficial effects on the immune response,generally in relation to allergies.Objective To assess the effect of Bifidobacterium lactis (B. lactis)supplementation on the presence of B. lactis and bifidobacteriacounts in stool of infants during the first 2 months of life .Methods We conducted an observational study of 122 healthy,breast-fed infants delivered vaginally or by Caesarean section.Infants assigned to the test group received breast milk and formulasupplemented with the B. lactis probiotics. Infants in the controlgroup received breast milk and formula without probiotics.The presence of B. lactis and stool bifidobacteria counts weredetermined at 1 month and 2 months of age. Growth, morbidity,serum immune markers, and stool immunoglobulin (lg) A werealso assessed.Results B. lactis was more frequently detected in the stool ofinfants who received breast milk and probiotic-supplementedformula than in stool of infants who received breast milk andnon-supplemented formula, both at 1 month and 2 months ofage (OR 1,263; 95%Cl 11 to 15 1,030; P=0.003) . Of infants whoreceived probiotic-supplemented formula, B. lactis was detected in80% of those delivered by Caesarean section and in 3 8% of thosedelivered vaginally, at the 1-month mark. In infants delivered byCaesarean section, the mean stool bifidobacteria level at 1 monthwas significantly higher in the probiotic-supplemented groupcompared to that of the non-supplemented group (P=0.021) .Conclusion Early bifidobacteria supplementation of infants,particularly those delivered by Caesarean section, is associatedwith higher levels of stool bifidobacteria. Anthropometric datasuggests beneficial effect s of bifidobacteria supplementationon infant growth, though most are not statistically significant.